Impact of mental imagery script timing on learning of playing patterns - Mguidich, H.; Ben Chikha, H.; Zoudji, B.; Khacharem, A. (German Journal of Exercise and Sport Research, 2026)
Mental imagery is a well-known technique in sports psychology that is often used to improve learning and performance among athletes. While its benefits are widely acknowledged, the specific impact of the timing of mental imagery—whether it should be practiced simultaneously with auditory instruction or sequentially—still remains to be clarified. A total of 100 basketball players, categorized into experts (n = 50) and novices (n = 50), were randomly assigned to either a simultaneous imagery condition (listening and imagining concurrently) or a sequential imagery condition (listening followed by imagining). The study revealed an expertise reversal effect, with novices benefiting more from the simultaneous imagery condition, whereas experts benefited more from the sequential imagery condition. The study concludes that the timing of mental imagery scripts significantly affects learning outcomes in athletes, with the efficacy of imagery timing depending on the individual`s level of expertise.